Reactive Oxygen Species Rewires Metabolic Activity in Acute Myeloid Leukemia - Robinson, Andrew J.; Davies, Sara; Darley, Richard L.; Tonks, Alex (Frontiers in Oncology, 2021)
Acute myeloid leukemia (AML) is a heterogeneous disease with poor clinical outcomes. We have previously shown that constitutive activation of NADPH oxidase 2 (NOX2), resulting in overproduction of reactive oxygen species (ROS), occurs in over 60% of AML patients. We have also shown that increased ROS production promotes increased glucose uptake and proliferation in AML cells, mediated by changes in carbohydrate metabolism. Given that carbohydrate, lipid, and protein metabolism are all intricately interconnected we aimed to examine the effect of cellular ROS levels on these pathways and establish further evidence that ROS rewires metabolism in AML. We carried out metabolomic profiling of AML cell lines in which NOX2-derived ROS production was inhibited and conversely in cells treated with exogenous H2O2. We report significant ROS-specific metabolic alterations in sphingolipid metabolism, fatty acid oxidation, purine metabolism, amino acid homeostasis and glycolysis. These data provide further evidence of ROS directed metabolic changes in AML and the potential for metabolic targeting as novel therapeutic arm to combat this disease.